Decolonizing arms control: the Asian African Legal Consultative Committee and the legality of nuclear testing, 1960–64. Issue 3 (2nd September 2018) - Abraham, Itty
ABSTRACT: This article seeks to contribute to a global history of disarmament by arguing for the importance of a largely forgotten moment in the history of arms control, namely, the report on the legality of nuclear testing issued by the Asian African Legal Consultative Committee (AALCC) in 1964. By focusing on the legality of nuclear testing during peacetime, the AALCC report was able to advance its objective of delegitimizing the possession of nuclear weapons without confronting the issue directly, a battle that militarily weak countries could not win. Using international law to compensate for political marginality was a novel anti-nuclear weapons strategy that would be adopted by other campaigns in decades to come. The article offers a critical genealogy of the dominant narrative of international arms control by situating the AALCC report within the historical context of decolonization and pointing out the importance of taking seriously the influence of global public opinion on superpower negotiating tactics. This approach adds a new dimension to our understanding of the global pressures shaping negotiations over the Partial Test Ban Treaty.